2022
DOI: 10.1002/ange.202202381
|View full text |Cite
|
Sign up to set email alerts
|

Pillararene‐Induced Intramolecular Through‐Space Charge Transfer and Single‐Molecule White‐Light Emission

Abstract: The fabrication of single‐molecule white‐light emission (SMWLE) materials has become a highly studied topic in recent years and through‐space charge transfer (TSCT) is emerging as an important concept in this field. However, the preparation of ideal TSCT‐based SMWLE materials is still a big challenge. Herein, we report a bifunctional pillar[5]arene (TPCN‐P5‐TPA) with a linear donor‐spacer‐acceptor structure and aggregation‐induced emission (AIE) property. The bulky pillar[5]arene between the donor and acceptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Through-space conjugated systems, , characterized as noncovalent structures with spatially delocalized π electrons, exhibited more flexibility and possibilities when compared with σ-bond-derived through-bond π conjugation. In particular, the beauty of their structures and their unique potential applications in optoelectronics and bioscience have attracted a lot of attention in recent years. From a structural viewpoint, the Q[8] cavity-confined π-conjugated aromatic molecules should belong to the family of through-space conjugated systems. , However, to the best of our knowledge, reports on through-space conjugated organic radicals via host–guest interactions are limited. Interestingly, when carboxylphenyl is used as the monosubstituted terminal moiety to the 4,4′-bipyridinium core to form guest McpV 2+ (Supporting Information), it was found that a different photochromism behavior was observed in the solution of the Q[8]/ McpV 2+ complex.…”
Section: Resultsmentioning
confidence: 99%
“…Through-space conjugated systems, , characterized as noncovalent structures with spatially delocalized π electrons, exhibited more flexibility and possibilities when compared with σ-bond-derived through-bond π conjugation. In particular, the beauty of their structures and their unique potential applications in optoelectronics and bioscience have attracted a lot of attention in recent years. From a structural viewpoint, the Q[8] cavity-confined π-conjugated aromatic molecules should belong to the family of through-space conjugated systems. , However, to the best of our knowledge, reports on through-space conjugated organic radicals via host–guest interactions are limited. Interestingly, when carboxylphenyl is used as the monosubstituted terminal moiety to the 4,4′-bipyridinium core to form guest McpV 2+ (Supporting Information), it was found that a different photochromism behavior was observed in the solution of the Q[8]/ McpV 2+ complex.…”
Section: Resultsmentioning
confidence: 99%
“…The minimal divergence of the olefinic group's (A = acceptor) dihedral angles from the attached benzene ring showed a conjugation of the phenolic −OH (D = donor) with the olefinic segment, favoring ITBC. In the rigid, nonconjugated pillar structure, on the other hand, like some reported structures, 51,52 the methoxy group containing the aromatic region of the backbone of 1 may serve as an electron donor to transfer the charge to the electron-deficient phenolic segment involving TSCT via through-space interaction. Thus, the macrocyclic structure 1 is an illustration that has the scope of ITBC and TSCT together.…”
Section: Single-crystal X-ray and Photophysical Studiesmentioning
confidence: 81%